Challenges in Food Security, Nutritional, and Social Public Policies for Venezuela: Rethinking the Future - Herrera-Cuenca, Marianella; Landaeta Jimenez, Maritza; Sifontes, Yaritza (Frontiers in Sustainable Food Systems, 2021)
Food Security has been impaired in Venezuela at individual, household, community and national levels. Food and nutrition systems have been compromised in the last decades, through the decreased food production and by the installation of food distribution networks that do not follow the policy and programs principles. These facts have had a negative impact on population wellbeing. Along with these changes, economic turndowns and political instability have been increasing, and a process of hyperinflation has been installed in the country, affecting people’s acquisitive power and increasing the poverty to the highest figures ever in recent Venezuelan history. The mode of production transition from a capitalist to a socialist State centered model, has been unsuccessful for increasing national production of foods, moreover, goods that traditionally were produced in Venezuela that used to cover the national needs, disappeared from the tables of Venezuelan people, introducing changes to the culinary traditions in the country, and the government’s network of distribution of foods is not efficient. For rethinking the future: reintroducing ethics and values and behavior changes in the population should be planned so new policies can be effective. In consequence to reestablish food security at households, holistic changes, aligned with nutritional needs, including the cultural traditional taste and respect of the human rights to food and health should be promoted to build a State policy that generates employment, through tourism, gastronomic initiatives, agriculture and food industry, while encouraging the establishment or recovery of certain laws and regulations for food qualities: the norms and rules for following the nutrition codex and establishing strong values to preserve health and good nutrition will be essential just to mention a few changes, in order to guarantee the diversity of foods, quality control, culinary traditions and nutritional needs of the population.